Spatial distribution and deployment of community-based distributors implementing integrated community case management (iCCM): Geographic information system (GIS) mapping study in three South Sudan states - Abigail Pratt; Martin Dale; Elena Olivi; Jane Miller (Edinburgh University Global Health Society, 2014)
In late 2012 and in conjunction with South Sudan's Ministry of Health - National Malaria Control Program, PSI (Population Services International) conducted a comprehensive mapping exercise to assess geographical coverage of its integrated community case management (iCCM) program and consider scope for expansion. The operational research was designed to provide evidence and support for low-cost mapping and monitoring systems, demonstrating the use of technology to enhance the quality of programming and to allow for the improved allocation of resources through appropriate and need-based deployment of community-based distributors (CBDs).